CBMT-49. OXALOACETATE ALTERS GLUCOSE METABOLISM IN GLIOBLASTOMA: 13C ISOTOPOMER STUDY. (11th November 2019) - Ijare, Omkar; Conway, David; Cash, Alan; Baskin, David; Pichumani, Kumar
Abstract: Anhydrous enol-oxaloacetate (AEO) has demonstrated the ability to enhance neuronal cell bioenergetics and activate brain mitochondrial biogenesis. Since oxaloacetate has demonstrated positive effects on brain bioenergetics in neurodegenerative diseases we have begun to investigate whether AEO may also have a positive effect on the altered cellular metabolism found in cancer cells, particularly Glioblastoma multiforme. The " Warburg effect " describes an abnormal metabolic state in cancer, distinct from normal tissue, in which energy is generated through enhanced conversion of pyruvate to lactate even in the presence of oxygen during glycolysis. Oxaloacetate (OAA) is a key anaplerotic substrate that is required to maintain TCA cycle flux. The role of oxaloacetate supplementation on the energy metabolism is not known in cancer cells. Goal of this study is to investigate the changes in metabolic fluxes in glucose metabolism with and without the presence of OAA in patient-derived GBM cells. We use GC-MS based 13 C isotopomer analysis for this study. GBM cells are grown in 15mM glucose containing DMEM medium supplemented with 2mM oxaloacetate for 10 days. 6 hours prior to harvesting, [U- 13 C]glucose is introduced to the medium. 13 C isotopomer analysis of GC-MS data showed that OAA supplementation for 10 days drastically decreased Warburg glycolysis by reducing 13 C labeling (M+3) by 19.7% and 48.8% in pyruvate and lactate pools respectively in comparison with cells not treated with OAA. M+3 13 C labeled pyruvate entered TCA cycle via acetyl-CoA, where we also observed reduced levels of M+2 13 C labeled citrate (20.5%) and glutamate (23.9%) isotopomers. Pyruvate can also enter TCA cycle via pyruvate carboxylation pathway and this activity was also found to be slightly decreased in the OAA treated cells. All the differences were statistically significant. These results indicate that OAA can be used to alter bioenergetics of GBM cells, specifically glucose oxidation.